Elucidation of Amyloid β-Protein Oligomerization Mechanisms: Discrete Molecular Dynamics Study - Urbanc, B. (J Am Chem Soc, 2010)
Oligomers of amyloid β-protein (Aβ) play a central role in the pathology of Alzheimer’s disease. Of the two predominant Aβ alloforms, Aβ(1–40) and Aβ(1–42), Aβ(1–42) is more strongly implicated in the disease. We elucidated the structural characteristics of oligomers of Aβ(1–40) and Aβ(1–42) and their Arctic mutants, [E22G]Aβ(1–40) and [E22G]Aβ(1–42). We simulated oligomer formation using discrete molecular dynamics (DMD) with a four-bead protein model, backbone hydrogen bonding, and residue-specific interactions due to effective hydropathy and charge. For all four peptides under study, we derived the characteristic oligomer size distributions that were in agreement with prior experimental findings. Unlike Aβ(1–40), Aβ(1–42) had a high propensity to form paranuclei (pentameric or hexameric) structures that could self-associate into higher-order oligomers. Neither of the Arctic mutants formed higher-order oligomers, but [E22G]Aβ(1–40) formed paranuclei with a similar propensity to that of Aβ(1–42). Whereas the best agreement with the experimental data was obtained when the charged residues were modeled as solely hydrophilic, further assembly from spherical oligomers into elongated protofibrils was induced by nonzero electrostatic interactions among the charged residues. Structural analysis revealed that the C-terminal region played a dominant role in Aβ(1–42) oligomer formation whereas Aβ(1–40) oligomerization was primarily driven by intermolecular interactions among the central hydrophobic regions. The N-terminal region A2-F4 played a prominent role in Aβ(1–40) oligomerization but did not contribute to the oligomerization of Aβ(1–42) or the Arctic mutants. The oligomer structure of both Arctic peptides resembled Aβ(1–42) more than Aβ(1–40), consistent with their potentially more toxic nature.